MiRNA-192 [corrected] and miRNA-204 Directly Suppress lncRNA HOTTIP and Interrupt GLS1-Mediated Glutaminolysis in Hepatocellular Carcinoma. - Yunxia Ge (PLoS Genetics, 2015)
Accumulated evidence demonstrated that long non-coding RNAs (lncRNAs) play a pivotal role in tumorigenesis. However, it is still largely unknown how these lncRNAs were regulated by small ncRNAs, such as microRNAs (miRNAs), at the post-transcriptional level. We here use lncRNA HOTTIP as an example to study how miRNAs impact lncRNAs expression and its biological significance in hepatocellular carcinoma (HCC). LncRNA HOTTIP is a vital oncogene in HCC, one of the deadliest cancers worldwide. In the current study, we identified miR-192 and miR-204 as two microRNAs (miRNAs) suppressing HOTTIP expression via the Argonaute 2 (AGO2)-mediated RNA interference (RNAi) pathway in HCC. Interaction between miR-192 or miR-204 and HOTTIP were further confirmed using dual luciferase reporter gene assays. Consistent with this notion, a significant negative correlation between these miRNAs and HOTTIP exists in HCC tissue specimens. Interestingly, the dysregulation of the three ncRNAs was associated with overall survival of HCC patients. In addition, the posttranscriptional silencing of HOTTIP by miR-192, miR-204 or HOTTIP siRNAs could significantly suppress viability of HCC cells. On the contrary, antagonizing endogenous miR-192 or miR-204 led to increased HOTTIP expression and stimulated cell proliferation. In vivo mouse xenograft model also support the tumor suppressor role of both miRNAs. Besides the known targets (multiple 5' end HOX A genes, i.e. HOXA13), glutaminase (GLS1) was identified as a potential downstream target of the miR-192/-204-HOTTIP axis in HCC. Considering glutaminolysis as a crucial hallmark of cancer cells and significantly inhibited cell viability after silencingGLS1, we speculate that the miR-192/-204-HOTTIP axis may interrupt HCC glutaminolysis through GLS1 inhibition. These results elucidate that the miR-192/-204-HOTTIP axis might be an important molecular pathway during hepatic cell tumorigenesis. Our data in clinical HCC samples highlight miR-192, miR-204 and HOTTIP with prognostic and potentially therapeutic implications.